ALIH PERANAN SURAU DALAM KEHIDUPAN MASYARAKAT MINANGKABAU DI KECAMATAN LIMA KAUM KABUPATEN TANAH DATAR - Arifan, Rahmat; Ibrahim, Bedriati; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Surau is one of the institutions that play an important role in the development of religious moral values as well as the cultural customs of Minangkabau, the success in educational process of Minangkabau children in surau is characterized by cleverness of recitation, obedience to worship, morals, and noble personality. The purpose of this research is to know (1) the role of surau in the life of Minangkabau society before the turn of the surau role in Lima kaum District. (2) the role of the surau in the life of the Minangkabau community after the role of surau in the district of Lima kaum. (3) factors influencing the role of surau to the life of the Minangkabau in Lima kaum District. (4) the role of a teacher in the surau before and after the overarching role of the surau in Lima kaum District. The method used in this research is qualitative. Data obtained from the interviews are then analyzed in their own language. The location of the research is the Lima kaum District Tanah DatarRegency. This research started from the beginning of the title of this researcher submitted until this thesis is completed. Data collection techniques used are observation techniques, documentation techniques, interview techniques and literature study techniques. The result of the research shows that surau as agent of cangeh has undergone a switching role which is caused by factors, namely, change of family system in Minangkabau society, change of pattern of merantau in Minangkabau society, existence of better education institution and absence of teacher.Keywords: Transition, Role, Surau